Fortifying Transparency: Enhancing Corporate Governance through Robust Internal Control Mechanisms - Manginte, Shofia Yunus (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study explores how robust internal control mechanisms enhance corporate governance by fostering organizational transparency and accountability. The focus is on the interplay between internal controls and corporate governance practices, emphasizing their collective role in promoting organizational success and sustainability. Research Design and Methodology: The study employs a qualitative approach, conducting a comprehensive literature review of peer-reviewed articles, books, and reports. Using relevant keywords, data were collected from academic databases such as PubMed, Scopus, Web of Science, and Google Scholar. Thematic analysis was used to categorize and synthesize recurring themes and patterns, ensuring objectivity and rigor in data interpretation. Findings and Discussion: The findings of this study have significant practical implications. They reveal that effective corporate governance frameworks, underpinned by robust internal control mechanisms, not only enhance transparency, accountability, and ethical conduct but also mitigate risks, safeguard assets, and ensure compliance with regulations. This underscores the real-world relevance of the research and its potential to guide organizational practices. Implications: This study highlights the need for organizations to comprehensively integrate internal control mechanisms into their governance frameworks. It also emphasizes the importance of fostering a culture of integrity, adopting technological innovations, and maintaining compliance with evolving regulations. However, the study also points to the need for future research, particularly longitudinal studies, and interdisciplinary approaches, to further understand the dynamic governance-control relationship. This opens opportunities for further exploration and the development of more effective corporate governance practices.